Influence of varieties, sheep manure and nitrogen on yield of cumin (Cuminum cyminum L.) - Singh, M Patidar, Balak Ram, M P Singh, Gopal (Journal of Spices and Aromatic Crops, 2004)
The performance of three varieties (Local, RZ-19 and RZ-209) of cumin (Cuminum cyminum) and the effect of sheep manure (0 and 5 t ha-1) and nitrogen levels (20 and 40 kg N ha-1) on the yield of the crop was evaluated at Jodhpur (Rajasthan). Growth and yield attributes, seed yield and net returns were significantly higher in improved varieties compared to local variety. Maximum seed yield (580 kg ha-1) and net returns (Rs 32,400 ha-1) were obtained with RZ-19. Application of sheep manure increased seed yield by 5.2% over no manure; however, net returns were not increased. Nitrogen @ 40 kg ha-1 significantly increased seed yield by 26 kg ha-1 and net returns by Rs 1850 ha-I with benefit-cost ratio of 2.19 over 15 kg N ha-1.